FIGURE OF SPEECH ON THE SONGS IN THE ALBUM GAJAH BY TULUS - Nadia Aurelia Dea Safira; Tris Trismanto (LINGUAMEDIA Journal, 2022)
The topic of this research is the use of figure of speech in three song lyrics. The title of this research is " FIGURE OF SPEECH ON THE SONGS IN THE ALBUM GAJAH BY TULUS ". The author chose three song titles as research data, the song entitled, “Sepatu”, “Gajah”, and “Jangan Cintai Aku Apa Adanya”. The reason the author chose this topic as research is because the lyrics of the songs on the album have a deep meaning, the songs have also received many awards at prestigious music events. The songs were also composed by Tulus who is the creator and singer of the songs based on some personal experiences in his life story. In this paper, the authors wrote using a qualitative descriptive method, in which the authors obtained research results by listening to songs that had been selected as a data source, then looking for pieces of song lyrics containing figure of speech, qualifying the types of figure of speech used in the lyrics of the song, then describe the meaning of the song lyrics that contain figure of speech Keywords: Figure of speech, Song, Music, Meaning, Lyric.